Demystifying the complexity and heterogeneity of recycling behavior in organizational settings: A mixed-methods approach. (December 2021) - Oke, Adekunle; McDonald, Seonaidh; Korobilis-Magas, Evagelos
Highlights: Recycling behavior is far from being the norm in organizational settings. Psychological factors alone do not foster for recycling in organizational settings. Contextual attributes are key determinants of recycling at work. Organizations can support recycling by making it less difficult to perform. Recycling schemes should be harmonized within and across local councils. Abstract: Research on recycling has advanced across different disciplines, although the current knowledge about recycling behaviors at the corporate level remains elusive. While most studies on recycling are focused on households, there is no indication that people who recycle at home engage in similar behavior when at work. To understand how to facilitate recycling at work, this study investigates recycling behavior at work and its antecedents. The study adopts a sequential exploratory mixed method (MM) approach as its methodological framework, using semi-structured interviews and statistical analysis through structural equation modelling (SEM). According to the findings, factors such as types and volumes of waste, responsibility/accountability, personal control, recycling schemes, institutional supports, and group harmony contribute to recycling behavior in organizational settings. The study demonstrates contextual attributes' contribution, particularly organizational support and social context of recycling to employees' recycling behavior. For recycling to be normative at the corporate level, this MM study argues for the need to harmonize schemes within and across contexts. There is a need to install similar recycling schemes and facilities within and across waste generation contexts to reduce the recycling complexity and maintain consistency in recycling behavior. This study's findings could assist waste planners and policymakers in designing effective waste management schemes that would contribute to the circular economy initiatives. We further discussed the implication of the study.